An Evaluation of the Historical Backdrop to the Role of Technology in Human Life - Sagar Kamath, Dr. Rajesh Babu (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
This study evaluates the historical evolution of technology and its profound role in shaping human life. Beginning with early tools and fire in prehistoric times, technology has continuously transformed societies, from the agricultural innovations of the Neolithic era to the engineering feats of ancient civilizations. The Industrial Revolution marked a turning point, introducing mechanization and mass production, while the 20th century saw accelerated advancements in communication, transportation, and electrification. The digital and information age brought unprecedented connectivity through the internet, social media, and mobile technology, revolutionizing daily life but also presenting challenges such as digital dependency and environmental concerns. This evaluation highlights the dual impact of technology—enhancing human potential while raising ethical, societal, and sustainability issues. As humanity faces the future, balancing innovation with responsibility will be key to ensuring technology serves as a force for progress and equity.